Beyond human capital explanations for the gender pay gap among executives: Investigating board embeddedness effects on discrimination - Jana Oehmichen; Maximilian A. Sarry; Michael Wolff (Business Research, 2014)
This paper examines the gender pay gap in top management teams and how it is affected by directors' embeddedness. We can reconfirm the result of previous studies that differences in managerial compensation between women and men exist, even after controlling for company properties and human capital attributes. Drawing on the language theory of discrimination, we then question how the embeddedness of directors-the actual deciders on executive compensation levels-affects the pay gap: embeddedness causing homophilous behavior resulting in a higher pay gap or directors using their network as knowledge source and decreasing the pay gap. We find evidence that knowledge effects outweigh potential homophily effects.
Keywords: J31; M12; J16; G30; 330; Gender pay gap; Management compensation; Language theory of discrimination; Network embeddedness; Women on management boards